[LB.03.07] COMPARATIVE EFFECTIVENESS CLUSTER-RANDOMIZED TRIAL OF A NURSE-LED TASK-SHIFTING STRATEGY FOR HYPERTENSION CONTROL VERSUS PROVISION OF HEALTH INSURANCE COVERAGE IN CHCS IN GHANA. (September 2017) - Ogedegbe, G.; Plange-rhule, J.; Gyamfi, J.; Chaplin, W.; Iwelunmor, J.; Ntim, M.; Apusiga, K.; Quakyi, K.; Mogavero, J.; Khurshid, K.; Tayo, B.; Cooper, R.
Abstract : Objective: Poor access to care and shortage of physicians are major barriers to hypertension control in sub-Saharan Africa. Evidence-based strategies targeted at these barriers are lacking. This cluster-randomized trial evaluated the comparative effectiveness of a nurse-led task-shifting strategy for hypertension control (TASSH) versus provision of health insurance coverage (HIC) alone on systolic blood pressure (SBP) reduction, lifestyle behaviors, and BP control in Ghana. Design and method: 32 community health centers (CHCs) were randomized to either HIC or TASSH+HIC. The HIC group received health insurance coverage plus scheduled nurse visits while TASSH+HIC group comprised the WHO cardiovascular risk management package including CV risk assessment; patient counseling on lifestyle modification, and initiation and titration of antihypertensive medications by trained nurses. Outcomes were mean SBP reduction at 12 months (primary); change in lifestyle behaviors and BP control at 12 months; and maintenance of SBP reduction at 24 months (secondary). Results: 757 patients (uncontrolled hypertension [mean BP 155.9 / 89.6 mmHg] without target organ damage; 60% women; and mean BMI 23) participated in the trial. In an intent-to-treat analysis with linear mixed effects regression model that adjusted for clustering, the TASSH+HIC group had a greater SBP reduction (−19.4 mmHg; 95% CI −17.2 to −21.6) versus the HIC group (−16.3 mmHg; 95% CI −13.5 to −19.1) with a statistically significant net difference of −3.6 mmHg [95% CI −6.0 to −0.5]. The SBP reduction was sustained for both groups at 24 months. Although the TASSH+HIC group had a higher BP control (55.2%) than the HIC group (49.9%), this difference was not significant (p = 0.292). Similarly, there was no difference in percent weight change and levels of physical activity at12 months between both groups. Conclusions: A nurse-led task-shifting strategy for hypertension control plus provision of health insurance coverage was more effective than health insurance coverage alone in SBP reduction among patients with uncontrolled hypertension in Ghana. These findings support implementation of the WHO CVD package in low-resource settings and provide the evidence for policy makers to recommend task-shifting as a viable strategy for hypertension control in sub-Saharan Africa.